PEER REVIEW - Study of Small Business Potential in Order to Emprower Small Enterpreneures in District Medan Deli - Dra. Dewi Andriany, M.M (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
PEER REVIEW - Study of Small Business Potential in Order to Emprower Small Enterpreneures in District Medan Deli